TOOLKIT FOR ENSURING FOOD SECURITY IN SHAPING THE SUPPLY OF AGRIFOOD PRODUCTS - PODSOKHA, Anna; KONONENKO, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the toolkit for ensuring food security at the stage of agrifood supply formation, focusing on its transformation amidst global and military challenges. It is substantiated that, in today's turbulent world, food security has moved beyond a narrow sectoral category to become a key element of national security, requiring the development of a comprehensive, adaptive, and multi-component toolkit for state regulation.The authors systematize and classify state-influence instruments by functional purpose, identifying four key groups: economic, legal, infrastructural, and institutional. The study explores the interconnectedness of these groups, demonstrating their synergistic effect: the effectiveness of one instrument (e.g., subsidies) depends on the existence and quality of another (e.g., infrastructure for storage and transportation).The analysis shows that there is no universal set of instruments; their optimal combination depends on external conditions. In periods of stable development, economic and market-oriented legal tools dominate, while in deep crises, such as the full-scale war in Ukraine, infrastructural and institutional instruments become paramount. The war served as a "stress test" for the food system, revealing its critical dependence on raw material exports and logistical concentration, which put the entire system at risk.The main conclusion is the necessity of a fundamental transformation of Ukraine's agrarian policy. The post-war recovery strategy should not aim for simple "rebuilding as it was" but for building a new, more resilient model with a dominance of deep processing, diversification, and decentralization of food systems. This requires a targeted application of investment, tax, regulatory, and infrastructural instruments to stimulate investment in the processing industry and the development of local supply chains.
Keywords: food security; state regulation; agricultural sector; toolkit; agrifood supply; wartime challenges; post-war recovery; sustainable development; infrastructural instruments; institutional instruments